2003
DOI: 10.4269/ajtmh.2003.69.141
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance Results From the First West Nile Virus Transmission Season in Florida, 2001

Abstract: After West Nile virus (WNV) was first detected in Florida in July 2001, intensive surveillance efforts over the following five months uncovered virus activity in 65 of the state's 67 counties with 1,106 wild birds, 492 horses, 194 sentinel chickens, and 12 people found infected with the virus. Thirteen of 28 mosquito isolations came from Culex mosquitoes. As seen in the northeastern United States, wild bird mortality was the most sensitive surveillance method. However, unlike the predominantly urban 1999 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(78 citation statements)
references
References 26 publications
(23 reference statements)
1
76
0
1
Order By: Relevance
“…Rather, that females were also affected is evidence disease may have played a part in the high mortality that year. Although West Nile virus did not reach Florida until 2001 (Blackmore et al 2003), many other mosquito-borne aviviruses were present in Florida during 1998 (Thomas et al 2003). Rainfall rates, mosquito abundance, and prevalence of encephalitic virus activity are correlated in Florida (Day and Alan 1989); thus, it is possible that high rainfall during 1998 and attendant increases in mosquito abundance could have increased exposure of Cooper's hawks to one or more of these aviviruses that year.…”
Section: Survival and Causes Of Mortalitymentioning
confidence: 99%
“…Rather, that females were also affected is evidence disease may have played a part in the high mortality that year. Although West Nile virus did not reach Florida until 2001 (Blackmore et al 2003), many other mosquito-borne aviviruses were present in Florida during 1998 (Thomas et al 2003). Rainfall rates, mosquito abundance, and prevalence of encephalitic virus activity are correlated in Florida (Day and Alan 1989); thus, it is possible that high rainfall during 1998 and attendant increases in mosquito abundance could have increased exposure of Cooper's hawks to one or more of these aviviruses that year.…”
Section: Survival and Causes Of Mortalitymentioning
confidence: 99%
“…nigripalpus and Cx. erraticus in southeastern parts of the United States (Blackmore et al 2003, Cupp et al 2007), and C. tarsalis across much of western North America , Turell et al 2005. Culex pipiens may also be important in urban areas in the western United States (Bolling et al 2007).…”
Section: Ecology Of Transmissionmentioning
confidence: 99%
“…It is interesting to note that this finding corresponds to the period when WNV was first detected in Florida in 2001. 29 Previous studies have suggested that introduction of WNV resulted in dramatic changes in the transmission of St. Louis encephalitis virus in Florida and elsewhere. 30,31 It is therefore possible that the introduction of WNV might have also affected the ecology of EEEV transmission in Florida, resulting in a shift in the predominant circulating viral type.…”
mentioning
confidence: 99%